2021
DOI: 10.2196/28089
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous System Maturation and Emotional Coordination in Interactions of Preterm and Full-Term Infants With Their Parents: Protocol for a Multimethod Study

Abstract: Background There is limited knowledge on the physiological and behavioral pathways that may affect the developmental outcomes of preterm infants and particularly on the link between autonomic nervous system maturation and early social human behavior. Thus, this study attempts to investigate the way heart rate variability (HRV) parameters are related to emotional coordination in interactions of preterm and full-term infants with their parents in the first year of life and the possible correlation wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Therefore, this is the reason why those systems should be assessed. In general, there is still not enough known about the relationship between the ANS and early social human behavior [ 26 ]. However, there is more and more research about it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this is the reason why those systems should be assessed. In general, there is still not enough known about the relationship between the ANS and early social human behavior [ 26 ]. However, there is more and more research about it.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is more and more research about it. For instance, Christina Koumarela et al (2021) investigated the regulatory role of the ANS and social reciprocity in preterm infants which may have big implications for the fields of medicine and psychology [ 26 ]. Another study showed that there are some methods which may help with ANS regulation.…”
Section: Introductionmentioning
confidence: 99%